Implementing of the Local Government Information System Policy in Financial Report Preparation For Local Government Units: A Case Study in Baubau City: IMPLEMENTATION - Amaruddin, Alvian Amar; Rasmuin; Rahmawati (Ilomata International Journal of Social Science, 2025)
This study explores the implementation of the Regional Government Information System (SIPD) in preparing financial reports of Local Government Units (SKPD)in the DPRD Secretariat of Baubau City. The study addresses how decentralized governance and transparency can be enhanced through e-government initiatives like SIPD, which integrates local financial data electronically. Despite clear policy guidelines outlined in various regulations, the research identifies challenges in human resource limitations, insufficient Standard Operating Procedures (SOPs), and inadequate infrastructure. Using a qualitative descriptive approach with interviews and document analysis, the study finds that although the implementation of SIPD supports transparency and accountability, its effectiveness is hindered by technical issues such as staff competency and system infrastructure. This research contributes to understanding public policy implementation, specifically within SIPD, while suggesting resource allocation and inter-departmental coordination improvements to enhance e-governance practices in local financial management.